Analisis Realisasi Penerimaan Pajak Kendaraan Bermotor Dan Bea Balik Nama Kendaraan Bermotor Pada Badan Pengelolaan Pajak Dan Retribusi Daerah (BPPRD) Provinsi Sumatera Utara - Fadilla Miranty; Juliana Nasution (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2022)
Regional taxes and obligations can be regarded as a source of income that plays an important role in the finance and administration of provincial governments and regional development. However, in reality, the realization of regional original revenue (PAD) is still experiencing many obstacles, as well as the effectiveness of the realization of motor vehicle tax (PKB) and motor vehicle title transfer fees (BBN–KB), which is caused by several factors. So, in this paper, researchers conducted a survey to analyze how the application of receipts for Motor Vehicle Tax (PKB) and Motor Vehicle Transfer Fees (BBN–KB). The writing of this research article uses one of the research methods, namely the qualitative method using a descriptive approach, while the data taken to write this article is interviews and observation reports on receipts of Motor Vehicle Taxes (PKN) and Motor Vehicle Transfer Fees (BBN-KB). using informational financial data through scientific articles related to this article. Based on the results of the study, it can be said that the performance of regional basic income (PAD) has increased and decreased between 2018 and 2021. And judging from the level of efficiency, receipts of Motor Vehicle Tax (PKB) and Motor Vehicle Transfer Fees (BBN-KB) are very efficient and have a positive trend, meaning that the budget execution situation is considered to be growing positively.Keywords : BBN – KB; PKB; Regional Original Revenue; Revenue Realization